Oncogenic and sorafenib-sensitive ARAF mutations in lung adenocarcinoma - Imielinski, Marcin (American Society for Clinical Investigation, 2014)

(untitled)
Targeted cancer therapies often induce “outlier” responses in molecularly defined patient subsets. One patient with advanced-stage lung adenocarcinoma, who was treated with oral sorafenib, demonstrated a near-complete clinical and radiographic remission for 5 years. Whole-genome sequencing and RNA sequencing of primary tumor and normal samples from this patient identified a somatic mutation, ARAF S214C, present in the cancer genome and expressed at high levels. Additional mutations affecting this residue of ARAF and a nearby residue in the related kinase RAF1 were demonstrated across 1% of an independent cohort of lung adenocarcinoma cases. The ARAF mutations were shown to transform immortalized human airway epithelial cells in a sorafenib-sensitive manner. These results suggest that mutant ARAF is an oncogenic driver in lung adenocarcinoma and an indicator of sorafenib response.